106k views
15 votes
8.5 Exercises

In Exercises 1-20 use the Laplace transform to solve the initial value problem. Where indicated by C/G, graph the solution.

#17.

y" + 3y' + 2y = {

e⁻ᵗ, 0 ≤ t < 1

0, t ≥ 1

y(0) = 1

y'(0) = - 1​

8.5 Exercises In Exercises 1-20 use the Laplace transform to solve the initial value-example-1
User Klepto
by
4.5k points

1 Answer

6 votes

We can express the forcing function (the piecewise expression on the right side) in terms of the step function as
e^(-t)(u(t) - u(t-1)) where


u(t) = \begin{cases}1&amp;\text{for }t\ge0\\0&amp;\text{otherwise}\end{cases}

Let F(s) be the Laplace transform of a function f(t). Now recall the transform pair


f(t-c) u(t-c) \mapsto e^(-cs) F(s)

This means


e^(-t) u(t) \mapsto \frac1{s+1}


e^(-t) u(t-1) = \frac1e * e^(-(t-1)) u(t-1) \mapsto &nbsp;(e^(-(s+1)))/(s+1)

I assume you're familiar with the transform rule for derivatives of y(t). Now we're ready to take the transform of both sides of the ODE:


y'' + 3y' + 2y = e^(-t)(u(t) - u(t-1))


\implies \left(s^2 Y(s) - s y(0) - y'(0)\right) + 3 \left(s Y(s) - y(0)\right) + 2 Y(s) = (1 - e^(-(s+1)))/(s+1)

Plug in the initial values and solve for Y(s) :


\left(s^2 Y(s) - s + 1\right) + 3 \left(s Y(s) + 1\right) + 2 Y(s) = (1 - e^(-(s+1)))/(s+1)


(s^2 + 3s + 2) Y(s) - s + 4 = (1 - e^(-(s+1)))/(s+1)


Y(s) = (1 - e^(-(s+1)) + (s-4)(s+1))/((s+1)(s^2 + 3s + 2))


Y(s) = (1 - e^(-(s+1)) + (s-4)(s+1))/((s+1)^2 (s+2))

Consider the partial fraction expansion


\frac1{(s+1)^2(s+2)} = \frac a{s+1} + \frac b{(s+1)^2} + \frac c{s+2}

Solve for the coefficients:


1 = a(s+1)(s+2) + b(s+2) + c(s+1)^2


s = -1 \implies b = 1


s = -2 \implies c = 1


1 = (a+c)s^2 + \cdots \implies a+c = 0 \implies a = -1

Hence we can expand Y(s) as


Y(s) = \frac1{(s+1)^2} + \frac1{s+2} &nbsp;+ (e^(-(s+1)))/(s+1) - (e^(-(s+1)))/((s+1)^2) - (e * e^(-(s+2)))/(s+2)

The last transform pair we need is


e^(ct) f(t) \mapsto F(s - c)

Now, taking inverse transforms of everything yields


\frac1{(s+1)^2} \mapsto te^(-t)


\frac1{s+2} \mapsto e^(-2t)


(e^(-(s+1)))/(s+1) \mapsto e^(-t) u(t-1)


(e^(-(s+1)))/((s+1)^2) \mapsto e^(-t) (t-1) u(t-1)


(e * e^(-(s+2)))/(s+2) \mapsto e^(-(2t-1)) u(t-1)

and putting everything together gives the same solution as the one provided.

User Stephan Vierkant
by
4.7k points